Using Simulations to Guide the Design of Amperometric Electrochemical Sensors Based on Mediated Electron Transfer - Elliott, JR; Le, H; Yang, M; Compton, RG (Wiley, 2020)
Mediated electron‐transfer sensors provide a practical means of detection for species for whom direct electron‐transfer sensors are impractical. Through the use of numerical simulation, the design and optimisation of mediated electron‐transfer sensors are presented in this work where we specifically consider the mediation as an irreversible process. Comparison is made between sensors employing the mediator as an adsorbed monolayer on the electrode's surface and sensors employing it as a soluble additive to the sample, with the former being concluded as preferable due to improved detection limits and practicality. Studies are performed for the optimisation of the electrode radius, mediating chemical rate constant and scan rate, with consideration also given to the capacitive current. Triangular and semi‐circular sweep voltammetry are compared in the context of mediating electron‐transfer sensor design. It is concluded that competition between the Faradaic and capacitive currents is a primary limitation for this technique.